ACTR-06. CLINICAL TRIAL OF VAL-083 IN NEWLY DIAGNOSED MGMT-UNMETHYLATED GBM: HALF-WAY REPORT. (11th November 2019) - Chen, Zhong-ping; Guo, Chengcheng; Yang, Qun-ying; Li, Jia-wei; Wu, Shao-xiong; Bacha, Jeffrey; Johnson, Gregory; Langlands, John; Kwan, Claire; Kanekal, Sarath; Schwartz, Richard; Lopez, Lorena; et al.
Abstract: Approximately 60% of glioblastoma multiforme (GBM) patients possess an unmethylated methylguanine DNA-methyltransferase (MGMT gene, which confers a limited response to standard of care treatment with temozolomide (TMZ) resulting in a lower survival. VAL-083 is a novel bi-functional DNA targeting agent that induces interstrand cross-links at N 7 -guanine, leading to DNA double-strand breaks and ultimately cell death. VAL-083 circumvents MGMT-mediated repair of the O 6 guanine alkylator TMZ. A Phase 2 study has been initiated for VAL-083 in newly diagnosed MGMT unmethylated GBM. The study has 2 stages: Stage 1 is a dose-escalation and induction format to confirm the recommended dose of VAL-083 when administered concurrently with radiation therapy (RT) based on safety and tolerability. The subjects received VAL-083 at 20, 30, or 40 mg/m 2 /day x 3 days every 21 days along with standard radiation treatment. Stage 2 comprises an expansion phase to enroll up to 30 patients. The dose escalation stage is complete and 30 mg/m 2 /day of VAL-083 in combination with RT was generally safe and well-tolerated. As of 17 May, 2019, 18 patients have been enrolled. Fifteen patients have completed their prospectively planned MRI scans and had their initial assessment for tumor progression. Of these 15 patients, seven were assessed as a complete response (CR), and eight patients as having stable disease (SD). Of the remaining three patients, one died prior to their post-cycle 3 MRI and two have not been on study long enough to reach their planned post-cycle 3 MRI. As of the data cutoff, 14 of the 18 patients were still alive. Consistent with our prior experience, myelosuppression was the most common adverse event. Three dose-limiting toxicities have been reported - one at the 40 mg/m 2 /day and two at the 30 mg/m 2 /day dose. Further enrollment, safety & study updates will be presented at the meeting. Clinicaltrials.gov identifier: NCT03050736.